The best of times, the worst of times. - Rosenzweig, Roy (Journal of Social History)
Focuses on the political attacks on social history. Attacks on a view of the past that is critical and inclusive; Contention that such attacks on the inclusiveness of history standards was brought about by social history's willingness to view the rich and powerful with less than the proper reverence; Unwillingness to celebrate American greatness; Charges of political correctness leveled by conservative politicians.